HUBUNGAN BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUANG NEONATUS RSUD BANGIL KABUPATEN PASURUAN - Idayanti, S.ST., M.Kes, Titiek (JURNAL KEPERAWATAN BINA SEHAT, 2016)
LBW is not handled properly could result in problems in all organ systems including respiratory disorders (meconium aspiration, asphyxia neonatorum. Asphyxia is a condition in which the newborn is not breathing spontaneously immediately after birth and regularly. Study aims to determine the relationship between low birth weight with neonatal asphyxia event in the Neonatus Room Hospital RSUD Bangil District, in 2016. The experiment was conducted in Januari - Februari 2016. This type of research in this study was observational, analytical research design that is corelasional crossectional approach. The population in this study is All neonates in the Neonauss Room Hospital RSUD Bangil District Januari – Februari 2016 a number of 112 neonates. Samples were taken with the technique of sampling a total of 112 samples. The independent variable in this study was the incidence of LBW in hospitals dr. Isaac Tulungagung district, while the dependent variable was the incidence of neonatal asphyxia in hospitals RSUD Bangil District. Data were analyzed by Chi Square test using SPPS program. The results obtained from a total of 112 deliveries majority of respondents were not experiencing BBLN and asphyxia neonatorum, as many as 62 deliveries (55.36%). Chi Square test statistic with a 0.05 earned significant p value 0.001 where 0.001 <0.05, so H0 is rejected and H1 accepted, meaning there is a relationship between the incidence of LBW in the incidence of neonatal asphyxia in Hospitals RSUD Bangil in 2016. High incidence of low birth weight and mortality due to complications such as one of asphyxia, infection, hypothermia, hyperbilirubinaemia. Infants with low birth weight / premature deficient growth of the tools in his body especially the lungs making it very sensitive to the impact on respiratory asphyxia.Keywords: The Corellation, LBW, Asphyxia Neonatorum